Advances on in vitro regeneration and microrhizome production in Zingiberaceae family - Subramanian, Meenakshi; Koh, Khong Shien; Gantait, Saikat; Sinniah, Uma Rani (Springer, 2024)
Zingiberaceae family, also known as the ginger family, comprises 53 genera and 1300 species. The members of this family are widely known for their ethnobotanical properties. Owing to their anti-inflammatory, antimicrobial, antidiabetic, and cardioprotective properties, the rhizomes have been used in traditional medicine to treat a wide range of illnesses like cold, inflammation, gastritis, arthritis, diabetes, and respiratory problems. The medicinal properties of the plants are attributed to the wide array of secondary metabolites present in them. They also find their use in food, spices, ornamentals, perfumes, and cosmetics. The current review focuses on biotechnological techniques like direct regeneration, indirect regeneration via callus induction and somatic embryogenesis, microrhizome induction, and in vitro secondary metabolite production that have been established to meet the increasing commercial and pharmaceutical demands. This review also identifies unrevealed possibilities, knowledge gaps, and considerable challenges that should be taken into account for developing novel concepts about the biotechnology of Zingiberaceae in the near future.